The history and evolution of gang scholarship: a topic modeling and change point detection approach - Gravel, Jason (The Oxford handbook of gangs and society, 2024)
This chapter examines turning points in the history of gang research published between 1834 and 2021. Using this database, trends in publication are examined using change point detection analysis to identify turning points in the productivity of gang scholars. Natural language processing (NLP) methods, topic modeling techniques, and scientometrics are used to explore the origin of these turning points and the evolution of subareas of interest in gang research. Gang scholarship evolved rapidly starting in the late 1980s, fostered by policy interests of the US federal government, exploded in the 1990s and 2000s with the availability of longitudinal data and the internationalization of gang research, and since the 2010s has continued to grow and to exhibit impressive diversity and increasing sophistication.